The Effect of Profitability and Leverage on Financial Distress with Inflation as Moderating - Safitri, Melania Galih; Yuliana, Indah (Jurnal ASET (Akuntansi Riset), 2021)
The purpose of this study was to determine the effect of profitability on financial distress and leverage on financial distress, as well as to determine whether inflation moderates the relationship between profitability and financial distress, and to moderate the relationship between leverage and financial distress in mining companies and consumer goods industry listed on the IDX in 2016-2019. This study uses secondary data in the form of annual financial reports and other supporting sources. The sampling technique used purposive sampling method as many as 48 out of 100 companies in the mining sector and consumer goods industry listed on the IDX. The analysis technique used is the Moderating Regression Analysis (MRA) test. The results showed that the variable profitability and leverage in 2016-2019 had a significant effect simultaneously and partially. This study also shows the results that inflation does not moderate the effect of profitability on financial distress and moderates the effect of leverage on financial distress.